2016
DOI: 10.1002/chem.201600323
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Metal–Support Interactions by Molybdenum Carbide: An Efficient Strategy toward the Chemoselective Hydrogenation of α,β‐Unsaturated Aldehydes

Abstract: Metal-support interactions are desired to optimize the catalytic turnover on metals. Herein, the enhanced interactions by using a Mo2C nanowires support were utilized to modify the charge density of an Ir surface, accomplishing the selective hydrogenation of α,β-unsaturated aldehydes on negatively charged Ir(δ-) species. The combined experimental and theoretical investigations showed that the Ir(δ-) species derive from the higher work function of Ir (vs. Mo2C) and the consequently electron transfer. In crotona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 75 publications
(173 reference statements)
1
31
0
Order By: Relevance
“…Szçllçsi et al appliedu ltrasonic irradiation to preparea series of Pt-based catalysts for the hydrogenation of CMA to CMO, and found that the selectivity towards CMO with the smaller particle size of Pt was higher than the one with the larger particle size of Pt. [62] This difference in the selectivity was explained in terms of the formation of effective metal-support active centers, which provided strong acceptors ites for C=O [63] crotonaldehyde towards crotyl alcohol, [64] and 4-nitrostyrolene towards 4-vinylaniline. [65] With similar particle size and metal loading, they attributed the pronounced enhancementso nboth hydrogenation activity and selectivity of catalysts to the strongm etal-supporti nteraction, during which the reported novel supports (H-MoO x and Mo 2 C) could donate (or gain) electrons to (or from) the active metal, thereby giving rise to superiorc atalytic performance.…”
Section: Resultsmentioning
confidence: 99%
“…Szçllçsi et al appliedu ltrasonic irradiation to preparea series of Pt-based catalysts for the hydrogenation of CMA to CMO, and found that the selectivity towards CMO with the smaller particle size of Pt was higher than the one with the larger particle size of Pt. [62] This difference in the selectivity was explained in terms of the formation of effective metal-support active centers, which provided strong acceptors ites for C=O [63] crotonaldehyde towards crotyl alcohol, [64] and 4-nitrostyrolene towards 4-vinylaniline. [65] With similar particle size and metal loading, they attributed the pronounced enhancementso nboth hydrogenation activity and selectivity of catalysts to the strongm etal-supporti nteraction, during which the reported novel supports (H-MoO x and Mo 2 C) could donate (or gain) electrons to (or from) the active metal, thereby giving rise to superiorc atalytic performance.…”
Section: Resultsmentioning
confidence: 99%
“…Density functional theoretical (DFT) calculation indicated that the hybridization between d‐orbitals of M and s‐ and p‐orbitals of C obviously broadened the d‐band of M, as exemplified by Mo 2 C ( Figure ) . The resulting d‐band state similar to that of Pt contributed to noble‐metal‐like catalysis, as well as strong metal–support interactions in carbide‐supported catalysts …”
Section: Fundamentals Of Her and Tmcsmentioning
confidence: 99%
“…As shown in Figure 4c, four peaks can be deconvoluted from the Ir 4f profiles, along with one assigned to Mo 4s at 66.8 eV.T he peaks at 61.6 and 64.6 eV were ascribed to 4f 7/2 and 4f 5/2 of Ir d + , [38] respectively,a nd those at 60.8 and 63.8 eV were associated with Ir 0 . [29,39] On the sample obtained at 200 8C, dominant Ir d + and negligible Ir 0 species were observed, which is ar esult of insufficient reduction at this temperature. As the temperature was improved for reduction,t he amount Figure 4d).…”
Section: Resultsmentioning
confidence: 94%